2019
DOI: 10.1038/s41598-019-55423-0
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural modeling of small angle scattering from photosynthetic membranes

Abstract: The last decade has seen a range of studies using non-invasive neutron and X-ray techniques to probe the ultrastructure of a variety of photosynthetic membrane systems. A common denominator in this work is the lack of an explicitly formulated underlying structural model, ultimately leading to ambiguity in the data interpretation. Here we formulate and implement a full mathematical model of the scattering from a stacked double bilayer membrane system taking instrumental resolution and polydispersity into accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 63 publications
(70 reference statements)
1
16
0
Order By: Relevance
“…The membrane thicknesses derived here (5.1 nm for dark-and 4.8 nm for light-adapted plants) are higher than the expected dimension for the thylakoid membrane. Neutron and x-ray scattering data for thylakoid membranes on leaves range from 3.4 to 4.8 nm (Jakubauskas et al, 2019). However, the light-induced shrinkage in membrane thickness derived in this study is statistically highly significant indicating that thinning of thylakoid membranes could control essential membrane functions.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The membrane thicknesses derived here (5.1 nm for dark-and 4.8 nm for light-adapted plants) are higher than the expected dimension for the thylakoid membrane. Neutron and x-ray scattering data for thylakoid membranes on leaves range from 3.4 to 4.8 nm (Jakubauskas et al, 2019). However, the light-induced shrinkage in membrane thickness derived in this study is statistically highly significant indicating that thinning of thylakoid membranes could control essential membrane functions.…”
Section: Discussionmentioning
confidence: 62%
“…The reason for this discrepancy is unclear as discussed in Ünnep et al (2014). However, a recent study where neutron scattering data were rigorously modeled revealed that the first Bragg peak (used to measure the grana repeat) is not a simple measure of the grana repeat distance (Jakubauskas et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, with 1.5 M NaSCN the decay of the periodic membrane ultrastructure was spectacularly accelerated; it was lost in less than 5 min ( Figure 7E). It is to be noted here, that these agents, including even NaCl, might have also induced changes in the microscopic structure of the membranes, affecting their form factor and thus their scattering length distributions, which could, in principle, be analyzed within an advanced mathematical model recently elaborated for cyanobacteria (Jakubauskas et al, 2019). This would require a detailed and systematic approach, paying also attention to the substantial differences between the ultrastructure of thylakoid membranes in cyanobacteria and higher plants; this is outside the scope of the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Part of such an experimental design is to estimate the scattering length densities of the sample material; however, calculating precise scattering length densities for biological systems is not straightforward, since the exact protein and lipid composition of the membrane, their volume fractions, protein H-D exchange degree, membrane-associated water content, and solvent composition need to be known. Some recently calculated scattering length density values of thylakoid membranes are given in Table 2 (Jakubauskas, 2016;Jakubauskas et al, 2019).…”
Section: Scattering Length Density and Contrastmentioning
confidence: 99%
“…There are currently about 40-50 works published on scattering from photosynthetic systems-photosynthetic bacteria, diatoms and other algae and of course from higher plants. Small-angle scattering has been used to investigate structure and dynamic changes of thylakoid membrane systems of plants (Finean et al, 1953;Kratky et al, 1959;Kreutz and Menke, 1960a;Kreutz and Menke, 1960b;Kreutz and Menke, 1962;Kreutz, 1963a;Kreutz, 1963b;Kreutz, 1964;Sadler, 1976;Li, 1979;Sadler and Worcester, 1982a;Sadler and Worcester, 1982b;Diederichs et al, 1985;Garab et al, 1997;Kirkensgaard et al, 2009;Nagy, 2011;Nagy et al, 2011;Nagy et al, 2013;Ünnep et al, 2014b;Herdean et al, 2016;Ünnep et al, 2017;Zsiros et al, 2020;Ünnep et al, 2020), protists (Sadler et al, 1973;Worcester, 1976;Sadler and Worcester, 1982a), diatoms (Nagy et al, 2011;Nagy et al, 2012), photosynthetic bacteria (Pape et al, 1974;Hodapp and Kreutz, 1980;Liberton et al, 2013b;Ünnep et al, 2014a;Li et al, 2016;Stingaciu et al, 2016;Eyal et al, 2017;Jakubauskas et al, 2019), algae (Nagy et al, 2011;Nagy...…”
Section: Introductionmentioning
confidence: 99%